Estudo da correlação do efeito de exchange bias com a magnetização reversa em ortocromitas do tipo Nd1-x(Pr,Dy)xCrO3 - Barbosa, Cristiane Cupertino Santos (2022)
In this work the structural and magnetic properties of the orthochomites Nd1-xPrxCrO3 (0 ≤ x ≤ 1) and Nd1-xDyxCrO3 (x = 0.05 and 0.20) compounds obtained by co-precipitation method were studied. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), magnetization measurements as a function of the temperature (MvsT) and magnetic field (MvsH). The samples Nd1-xPrxCrO3 exihibit a single phase with orthorhombic symmetry, Pnma space group and slight changes in the structural parameters as a function of the Pr3+ concentration. EDS results confirm the incorporation of Pr3+ ions into structure consistent with nominal concentration of the samples. MvsT curves show a gradual increase in the antiferromagnetic phase transition temperature of the Cr sublattice as a function of increasing Pr3+ concentration. Furthermore, spin reorientation temperature (TRS ≈ 35 K) of the sample x = 0 is suppressed with the addition of the Pr3+ dopant. Below Néel temperature, compensation temperature and magnetization reversal are observed for samples between 0.15 ≤ x ≤ 0.60, suggesting that the non-Kramer Pr3+ ion may play an important role in the magnetic properties of the system. MvsH measurements show the presence of a antiferromagnetic state accompanied by a weak ferromagnetic contribution and conventional (ZFC) and spontaneous (FC) exchange bias (EB) effects. The sign of the exchange bias field (negative and positive) and magnetization reversal can be tunning by the Pr3+ concentration, temperature and cooling magnetic field, indicating a strong correlation between them. Both EB and MR show a dependence on the absolute value of the total magnetization of the rare earth ion sublattice. In addition, the particle-size effects on the magnetic properties were investigated in the Nd0.5Pr0.5CrO3 and Nd1-xDyxCrO3 samples calcined at different temperatures. XRD data and SEM images show clearly in both cases an increase in particle sizes as a function of the calcination temperature. Furthermore, no significant changes were observed in Néel temperatures with increasing calcination temperature. In particular case of the Nd0.5Pr0.5CrO3 sample, it is observed a increase in the compensation temperature with increasing particle size. The MvsH curves indicate the presence of the phenomenon of positive and negative EB for the samples doped with Pr and Dy, respectively. Exchange bias field values increase with particle size reduction. This behavior may be associated to a variation in the fraction of ferromagnetic clusters on the surface of the particles and in the antiferromagnetic spins into core.